Edge Computing Revolution: Architecting the Future of Distributed Infrastructure - Sai Prasad Mukala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
VMware’s Edge Computing and Emerging Technologies are transforming modern IT infrastructure by enabling organizations to process data closer to the source, reducing latency and enhancing performance for distributed workloads. This comprehensive article encompasses the Edge Compute Stack (ECS), which provides a lightweight, scalable solution for deploying virtual machines at the edge across industries such as retail, manufacturing, and telecommunications. The integration of AI and machine learning capabilities, powered by GPUs, enables advanced analytics while maintaining data sovereignty in compliance with regional regulations. VMware’s multi-cloud strategies strengthen edge deployments by ensuring workload mobility and disaster recovery across environments. Future technological advancements include ARM-based deployments, quantum-safe encryption, and self-healing infrastructure. Real-world applications demonstrate tangible benefits in retail inventory management, manufacturing predictive maintenance, and telecommunications service delivery. VMware’s security approach incorporates multiple protection layers through micro-segmentation and zero-trust principles, while the Sovereign Cloud framework addresses data governance systematically across distributed environments.